Pemberdayaan kelompok santri Trash Hero melalui pengolahan plastik non-recycle menjadi Paving Block ramah lingkungan - Mukminah, Mukminah; Septiani, Baiq Dewi Sukma; Riana, Riana (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2024)
Managing non-recyclable plastic waste has become a major challenge in preserving the environment, particularly in educational settings such as Madrasah Aliyah Nurul Ulum. To address this issue, a community service program was conducted with the aim of enhancing students' knowledge and skills in processing non-recyclable plastic waste into eco-friendly paving blocks. The program employed several methods, including Focus Group Discussions (FGD), outreach, training, technology application, mentoring, evaluation, and program sustainability. The results demonstrated a significant improvement in students' understanding and skills. Pretest scores averaged 2.2 for knowledge of non-recyclable plastic waste, which increased to 4.5 in the posttest. Understanding of the environmental impact of non-recyclable plastic waste improved from 2.5 to 4.7, while skills in making paving blocks increased from 1.4 to 4.1. Moreover, awareness of sustainable waste management rose from 1.7 to 4.2, and the willingness to continue paving block production improved from 1.2 to 3.9. This program successfully educated the surrounding community and provided a tangible solution to reduce environmental pollution. The program's sustainability is supported by the Trash Hero student group, which actively continues the plastic waste processing activities to produce paving blocks for use within the school environment.